ADAPTATION OF THE INDONESIAN VERSION OF THE WORK REGULATORY FOCUS SCALE - Rahmi, Tuti; Agustiani, Hendriati; Harding, Diana; Fitriana, Efi (Faculty of Psychology, Universitas Diponegoro, 2023)
This current study aims to adapt the Work Regulatory Focus Scale into the Indonesian version, following the International Test Commission (ITC) Guidelines for Test Adaptation. Thisis cross-sectional study involved 218 participants from a local bank with several branches in Indonesia. Confirmatory Factor Analysis using Lisrel 8.80 was employed to analyze the data. Regulatory focus and work engagement are correlated to determine convergent validity, while CR (Construct Reliability) evaluates reliability. The results of the Confirmatory Factor Analysis indicate that the Work Regulatory Focus Scale model fits the data best (RMSEA = .073, NFI = .94, CFI = .96, Standardized RMR = .065, and AGFI = .93, p = .000). The scale also demonstrates good reliability, with a CR value of .798 for promotion focus and .778 for prevention focus. Furthermore, a relationship between work regulatory focus and work engagement was found. These findings indicate that the Work Regulatory Focus has good psychometric properties and provides supports for applicability in the Indonesian context.